Lifestyle Dynamics and Purchasing Pattern Transformation: Significant Shifts in Indonesian Society Post-Pandemic - Bachtiar , Muchamad; Panji, Kemas A. Rachman; Sufa, Siska Armawati; Amani, Sabila Zata; Mayangsari , Ayulina (PT. Riset Press International, 2024)
The COVID-19 pandemic has deeply impacted Indonesia, leaving lasting effects on both public health and societal norms. Beyond mere statistics, the transformation touches every aspect of life, altering how Indonesians work, live, and connect with the world. Accelerated digital adoption, increased health consciousness, and a shift in priorities have significantly reshaped the consumer landscape. E-commerce platforms have boomed, serving as virtual marketplaces for various needs. A holistic approach to well-being emerged, with a focus on organic foods, fitness, and mindfulness. Environmental concerns spurred a demand for sustainable products. The allure of material possessions diminished, replaced by a desire for meaningful experiences and personal growth. This intricate tapestry reveals a post-pandemic Indonesia emphasizing technology, health, sustainability, and a redefined pursuit of happiness. Businesses and policymakers must comprehend these shifts to adapt strategies for the evolving consumer, fostering responsible consumption and contributing to a better Indonesia.